"In‐Situ Grown Nickel‐Cobalt (NiCo) Alloy Nanoparticles Decorated on Petal‐Like Nitrogen‐Doped Carbon Spheres for Efficient OER Activity". Issue 11 (17th March 2022) - Ali, Zulfiqar; Mehmood, Mazhar; Aslam, Muhammad; Haider, Muhammad Arslan
Abstract: Herein, we report in‐situ NiCo alloy nanoparticle formation of extremely small diameter (1–5 nm) on nitrogen (N)‐doped carbon spheres by the CVD method at 750 °C temperature, followed by its use in oxygen evolution reaction (OER) electrocatalysis. Secondary electron microscope (SEM) imaging shows the open as well as close cup‐shaped spheres and discs, while transmission electron microscope (TEM), X‐ray diffraction (XRD) and X‐ray photoelectron spectroscopy (XPS) studies confirmed the ultrafine NiCo alloy particles′ formation on nitrogen‐doped multilayer graphitized carbon. Moreover, Raman spectroscopy revealed the ID /IG ratio to be about 1.57 for N‐doped graphitic multilayer carbon, thereby suggesting the defective nature of graphitized carbon material, which may possibly be due to the incorporation of nitrogen atoms into graphitic carbon layers. The formation of extremely small NiCo alloy nanoparticles is attributed to the reducing carbonaceous environment of CVD constituted by ethanol and acetonitrile precursors, while carbon spheres/disks seem to be catalysed by silica substrate originated from an alcogel catalyst. In addition, synthesised hybrid nanocomposites materials were tested for OER electrocatalysis in alkaline conditions and it was found that synthesized NiCo alloy nanoparticles decorated on N‐doped carbon spheres have an overpotential 310 mV at current density of 10 mA/cm 2 which is just 5 mV higher than that of benchmark Ir/C (20 wt % Ir) electrocatalyst. The multiphase components of synthesised material like; electrically conductive carbon, nitrogen‐doped sites and well‐separated ultrafine NiCo alloy nanoparticles synergistically contributed towards better OER activity in alkaline conditions. Abstract : Ultrafine NiCo alloy nanoparticles decorated on nitrogen doped graphitic carbon spheres (NiCo‐NCS) have been synthesized by chemical vapour deposition (CVD) method at growth temperature of 750 °C. The NiCo alloy nanoparticles/nanoclusters were formed in‐situ amidst reducing environment of CVD without prior treatment of NiCo‐chloride alcogel. The unique features of the grown nanohybrid material were found to be beneficial for oxygen evolution reaction (OER) activity in alkaline media. Moreover, NiCo‐NCS and Ir/C (20 wt % Ir) showed comparable electrochemical performance under similar conditions.